Need of Traceable Force Measurements in Steel Industry in Meganewton Level Forces# - FANK, Sinan (International Journal of Computational and Experimental Science and Engineering, 2016)
In mechanical engineering, aerospace industry, energy industry, builting industry, safety engineering and testing, forces with nominal values in excess of 15 MN are measured. When we come to steel industry, need of MN level force measurements reach up to 100 MN level forces. Especially in rolling, pressing and extrusion process in steel and iron industry uses the MN level forces which are used in process control and development of high quality products. For this reason, MN level force should be measured reliably and accurately in iron and steel industry for repeatable products. In order to get reliable and accurate measurement results from the force measuring devices, they need calibrations traceable to international force standards. In this study, needs on MN level force measurements in iron and steel industry and subjects on traceable force measurements will be discussed.